2005
DOI: 10.1142/s0218810405002516
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the Flexor Digitorum Profundus Tendon to the Small Finger Within the Carpal Tunnel

Abstract: We report three patients who sustained a rupture of the flexor digitorum profundus tendon to the small finger within the carpal tunnel. There was a common mechanism of injury, each rupture occurred during resisted flexion of the digit with the metacarpophalangeal joint in extension. All the patients were male, one patient had an asymptomatic undiagnosed fracture of the hook of hamate, one patient had radiological evidence of piso-triquetral osteoarthritis. In each case, an attrition rupture was confirmed at su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Folmar et al 30 reviewed 12 flexor tendon ruptures in nonrheumatoid hands and found that all were caused by pathologic states, such as a nonunion fracture of the lunate, exostosis of the distal radius, and chronic synovitis. Other causes of intratendinous flexor tendon rupture previously described in the literature include, and are not limited to, osteoarthritis of the pisotriquetral joint, 31 nonunion fracture of the hook of the hamate, 32 lunate dislocation, 33 accessory carpal bone, 34 gouty infiltration of the flexor tendon, 35 and tumor. 36 In 1991, Kannus and Jozsa 3 evaluated tendon specimens from 5 different sites after spontaneous ruptures in 891 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Folmar et al 30 reviewed 12 flexor tendon ruptures in nonrheumatoid hands and found that all were caused by pathologic states, such as a nonunion fracture of the lunate, exostosis of the distal radius, and chronic synovitis. Other causes of intratendinous flexor tendon rupture previously described in the literature include, and are not limited to, osteoarthritis of the pisotriquetral joint, 31 nonunion fracture of the hook of the hamate, 32 lunate dislocation, 33 accessory carpal bone, 34 gouty infiltration of the flexor tendon, 35 and tumor. 36 In 1991, Kannus and Jozsa 3 evaluated tendon specimens from 5 different sites after spontaneous ruptures in 891 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, Grant et al . [ 4 ] published a case series of three attrition ruptures to the FDP little finger caused by the hamate bone.…”
Section: Discussionmentioning
confidence: 99%
“…Elles reproduisent une anomalie anatomique le plus souvent ignorée et bien tolérée. La greffe tendineuse du FDP du cinquième, utilisant le palmaris longus (PL) donne de bons résultats dans la littérature [2,3,8,18]. Nous n'en avons pas l'expérience.…”
Section: Discussionunclassified
“…Cette usure se fait sur une irrégularité osseuse qui peut être : -une apophyse unciforme rugueuse de l'os crochu. Le premier cas a été décrit par Boyes en 1960 [1], nous en rapportons six nouveaux qui s'ajoutent aux travaux précédents [8,10,[17][18][19] ; -une calcification du fibrocartilage triangulaire [7] ; -une articulation pisitriquétrale arthrosique peut être également responsable d'une rupture du FDP du cinquième doigt [3] ; ○ les ruptures par anomalie anatomique. Il s'agit d'un tendon unique pour les fléchisseurs profonds des quatrième et cinquième doigts qui se divise en deux en amont du lombrical [4,6,12].…”
Section: Discussionunclassified